2022
DOI: 10.1002/prep.202100358
|View full text |Cite
|
Sign up to set email alerts
|

An Answer to the Question about the Energetic Performance of TKX‐50

Abstract: Some of the relevant detonation performance parameters of TKX-50 were re-determined. The enthalpy of formation was obtained from the measured heat of combustion to be ΔH°f (TKX-50(s)) = + 213.4 � 1.2 kJ mol À 1 . The heat of detonation was measured to be 4650 � 50 kJ kg À 1 . The detonation velocity of a TKX-50/wax mixture (97 : 3) at a density of 1.74 g cm À 3 was found experimentally to be 9190 m s À 1 . Using the experimentally obtained enthalpy of formation for TKX-50 of + 213.4 kJ mol À 1 and the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The experimentally determined (combustion calorimetry) value of Sinditskii of (111 � 16) kJ • mol À 1 [8] appears to be too low and the original reported value (combustion calorimetry) of 439 kJ • mol À 1 is too high [1,12]. The other experimentally determined results [6,9,10,11] given in Table 2 are all relatively similar and result in an average value D f H � m ðcrÞ of 197.4 kJ • mol À 1 . This is considerably lower than calculated value of 447 kJ • mol À 1 originally reported [1,7,12].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The experimentally determined (combustion calorimetry) value of Sinditskii of (111 � 16) kJ • mol À 1 [8] appears to be too low and the original reported value (combustion calorimetry) of 439 kJ • mol À 1 is too high [1,12]. The other experimentally determined results [6,9,10,11] given in Table 2 are all relatively similar and result in an average value D f H � m ðcrÞ of 197.4 kJ • mol À 1 . This is considerably lower than calculated value of 447 kJ • mol À 1 originally reported [1,7,12].…”
Section: Introductionmentioning
confidence: 87%
“…However, the same cannot be said for the heat of formation of TKX‐50, which has resulted in a plethora of values and discussion as to not only which value is best, but also which method should be used to calculate the enthalpy of formation of such a compound [7–12]. There is a large discrepancy between the value for the enthalpy of formation ( ΔfHnormalm ${{\rm{\Delta }}_{\rm{f}} H_{\rm{m}}^{^\circ} }$ (cr)) ${({\rm { cr))}}}$ originally reported (447 kJ ⋅ mol −1 calculated [1, 7], 439 kJ ⋅ mol −1 combustion calorimetry) [7, 12] and more recently reported experimental and calculated values which are given in tables 2 and 3 respectively [6, 8–12].…”
Section: Introductionmentioning
confidence: 99%
“…When measuring the heat of detonation, it is necessary to use TKX-50 of high purity. Therefore, for calorimetric measurements, charges containing no binder were prepared, despite the fact that they are characterized by low mechanical strength [5]. The powdery samples were pressed (at 100 MPa) into approx.…”
Section: Methodsmentioning
confidence: 99%
“…Among nitrogen-rich heterocycles, the tetrazole ring is an attractive scaffold for the design of various energetic materials due to its high thermal stability, good detonation characteristics, and high resistance to various kinds of actions (both of mechanical and chemical nature). An introduction of the N -oxide motif (or a hydroxyl group in the case of a neutral compound) into the structure of tetrazole salts enables further improvement of the properties of compounds by varying the structure and optimizing the desired characteristics. In this connection, bistetrazole dioxides and their salts are considered as highly promising energetic materials due to their high enthalpies of formation and, in turn, high detonation characteristics. Thus, in particular, for dihydroxylammonium bistetrazole 1,1-dioxide (TKX-50, 1b ), the enthalpy of formation was determined to be 107 kcal mol –1 . However, subsequent experimental tests showed that the enthalpy of formation is 50 kcal mol –1 lower than originally estimated. , …”
Section: Introductionmentioning
confidence: 99%